Identity and adulthood - Kakar, Sudhir (Oxford University Press, 1979)
Selection of papers discussed at a seminar held by the Indian Council of Social Science Research in Delhi, 1977; includes the text of the 1st Vikram Sarabhai Memorial lecture.